1-[(2-Chlorophenyl)diphenylmethyl]-1H-pyrazole - Pierre Koch; Dieter Schollmeyer (IUCrData)
The title compound C22H17ClN2, also named as TRAM-34, crystallizes in the monoclinic space group P21/n. The dihedral angles between the pyrazole ring and the three six-membered rings are 62.28 (9), 69.48 (9) and 71.30 (9)°.